PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PT. SINARMAS MULTIFINANCE CABANG SORONG - Emilia Dian Iriany; Andrey Maryen; Agnes Banea (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This research aims to determine the quality of service to customer satisfaction of PT.Sinarmas Multifinance which can be measured by :1. Tangibles , 2. Reliability, 3.Responsiveness 4.Asurance, 5.Emphaty. This research uses a quantitative research approach with an observation approach and the distribution of questionnaires ,with a sampel of 50 customers of PT.Sinarmas Multifinance Sorong City barnch. Using data analysis techniques : 1.simple linear regression analysis, 2. T test, 3.test the coefficient of determination (R2). The result of linear regression analysisi obtained the aquation Y = 5.675 + 0.695 X. where a =5.675 is a constant value,assuming that if the service increases by 1,there is an increase in customer satisfaction value of 0.695. The results of the analysis r^2 = 0.506 or 50.6%, which means that customer satisfaction is 50.6% influenced by the quality of service to customer of PT.Sinarmas Multifinance Sorong City branch ,while the remaining 49.4% is determinend by other variables not examinend in this study.